Legal training of students in medical schools - А. А. Kablukov; O. Р. Strakhova (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2014)
Legal training of medical workers is an urgent problem that must be solved in order to improve the comprehensive process of teaching students at the Ukrainian medical schools. An example of implementation the initial stage of legal training for medical students based on existing training programs, within existing departments is described in this article. The acquisition of the primary skills for students in fi nding and selecting the legal documents and the ability to navigate skillfully in the chosen material is the result of the introduction of legal content information systemsinto the studying curriculum.